Forecasting the potential impact of cell and gene therapies in France: projecting product launches and patients treated - Lee, Ming Kei; Seyedmousavi, Sama; Auvity, Sylvain; Pourroy, Bertrand; Elleboode, Vincent; Kachaner, Isabelle; Jansen, Christel; Lilliu, Herve (Frontiers in Medicine, 2024)
Objective To evaluate the potential impact of cell and gene therapies (CGTs) in France by forecasting the number of patients that will be treated with CGTs over the period 2023–2030 by therapeutic area and region. Methods A review of CGTs in clinical development and related disease epidemiology was conducted to forecast the number of CGT launches and patient population between 2023 and 2030. The number of expected launches was identified by filtering the clinical development pipeline with estimated time to launch and probability of success values from Project ALPHA. Disease prevalence and incidence in France were combined with projected adoption rates derived from historical data to forecast the patient population to be treated. Results Up to 44 new CGTs are forecasted to launch in France in the period 2023–2030, which translates into more than 69,400 newly treated patients in 2030. Leading indications in terms of newly treated patients per year include cardiovascular disease, hematological cancers and solid tumors with 27,300, 15,200 and 13,000 newly treated patients in 2030, respectively. Discussion The forecast suggests that the future landscape of CGTs will undergo a shift, moving from CGTs targeting (ultra) rare diseases to more prevalent diseases. In France, this will likely pose organizational challenges hindering patient access to these transformative therapies. Further research and planning around network organization and patient distribution are needed to assess and improve the readiness of the French healthcare system for ensuring access for this growing number of patients to be treated with CGTs.